2013
DOI: 10.1002/cbi3.10014
|View full text |Cite
|
Sign up to set email alerts
|

ENaC, iNOS, mucins, and wound healing in cystic fibrosis airway epithelial and submucosal cells

Abstract: We compared airway epithelial cell models relevant for cystic fibrosis (CF): 16HBE cells with endogenous wild-type cystic fibrosis transmembrane conductance regulator (CFTR), CFBE cells with mutated DF508-CFTR, corrected CFBE cells overexpressing CFTR, CFSME (CF submucosal) and Calu-3 (non-CF submucosal) cells with respect to the epithelial sodium channel (ENaC), inducible NO synthase (iNOS) and mucins (MUC) (studied by quantitative Real-Time-Polymerase Chain Reaction, qRT-PCR and Western blot), and wound heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…2A ). These epithelial cells produce the mucins MUC1, MUC2, MUC4, and MUC5B ( 37 , 38 ). Once biofilms developed, the coculture was treated with a dispersal agent, such as sodium nitrite, for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…2A ). These epithelial cells produce the mucins MUC1, MUC2, MUC4, and MUC5B ( 37 , 38 ). Once biofilms developed, the coculture was treated with a dispersal agent, such as sodium nitrite, for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth to note that cell proliferation and migration were not assayed in wounded conditions [ 165 ], differently from other studies which nevertheless found a difference in cell migration during wound repair, as noted above. Interestingly, CFTRinh-172 induced a delay in wound repair, not only in non-CF cells (16HBE and corrected CFBE cells) but also in CFBE monolayers [ 165 ], indicating that this effect may not be related to the ion channel function of CFTR, but most probably is an unspecific effect of the inhibitor. A non-specific effect of CFTRinh-172 has also been found in other cell types of airway and non-airway origin [ 185 ].…”
Section: Airway Epithelial Regeneration Wound Repair and Cfmentioning
confidence: 92%
“…Ex-vivo xenograft models have been used in the context of re-differentiation of a native airway epithelium leading to regeneration and mucosa reconstitution by basal-like cells [ 161 ]. On the other hand, in-vitro models have been used to study wound repair through simplistic models of injury and repair [ 138 , 162 , 163 , 164 , 165 , 166 ]. These studies have been mainly conducted in submerged cultures on plastic, with either immortalized or primary cells lines, leaving aside all the fact that in vivo we deal instead with a polarized pseudostratified airway epithelium.…”
Section: Airway Epithelial Regeneration Wound Repair and Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…U87 and U251 cells (1×10 6 cells/well) were seeded into 6-well plates. After reaching 70% confluence, the cells were transfected with miR-10b-5p mimic or inhibitor, and incubated for 48 h. Using a 200-µl sterile pipette tip, three scratches were created in each well (15). Next, the cells were washed twice with PBS and incubated in medium supplemented with 2% FBS for 24 h. In order to assess the cell migration, images of the wells were captured at 0 and 24 h in three randomly selected microscopic fields (Olympus Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%